Sugar-Sweetened Beverage Consumption and Risk of General and Abdominal Obesity in Iranian Adults: Tehran Lipid and Glucose Study - Parvin MIRMIRAN; Hanieh-Sadat EJTAHED; Zahra BAHADORAN; Sara BASTAN; Fereidoun AZIZI (Tehran University of Medical Sciences, 2015)
Background: General and abdominal obesity are major global health problems. This cross-sectional study was conducted to evaluate the association between consumption of sugar-sweetened beverages (SSBs) and body mass index and waist circumference status in 5852 Iranian adults within the framework of the Tehran Lipid and Glucose Study (TLGS). Methods: Intakes of SSBs including carbonated drinks and synthetic fruit juices were measured using a validated food frequency questionnaire. The association between body mass index, waist circumference and body adiposity index in each quartile category of SSB consumption were determined using the multivariable linear regression models. The odds ratio (OR) of general and abdominal obesity in each quartile of SSB consumption was also determined using the multivariable logistic regression models. Results: Mean dietary intake of SSBs was 48.9 g/d or 0.25 servings/d. After adjustment for all potential confounding variables, significant associations were observed between SSB consumption and BMI (β: 0.49, 95% CI: 0.13-0.86), and waist circumference (β: 1.28, 95% CI: 0.40-2.16) in the fourth quartile. There was no significant association between SSB consumption and body adiposity index. Participants who consumed > 57.1 g/d of SSBs had 22% higher risk of general obesity (OR: 1.22, 95% CI: 1.00-1.48) and 35% higher risk of abdominal obesity (OR: 1.35, 95% CI: 1.12-1.61), compared with those in the lowest quartile of SSB consumption. Conclusion: Higher intakes of SSBs were associated with the higher risk of general and abdominal obesity in adults suggesting that limiting the consumption of SSBs may be a practical approach to prevent and manage obesity.   Keywords: Sugar-sweetened beverages, Obesity, Abdominal obesity, Iran